Structural and functional study of yeast nucleosome assembly protein 1 - Park, Young jun, author; Luger, Karolin, advisor; Peersen, Ovle, committee member; Laybourn, Paul, committee member; Anderson, Oren P., committee member; Woody, Robert W., committee member (Colorado State University. Libraries, 2005)
At one time nucleosome was considered a very static structure that packs DNA into the nucleus. However, the data in the last 15 years suggest that nucleosomes are highly dynamic macromolecular complexes that are assembled and disassembled by various factors. One important way in which this dynamic process can be modulated is by the replacement of major histones with their variants, thereby affecting nucleosome structure and function. One of the essential histone H2A variants is H2A.Z that is conserved from yeast to humans. The early observation suggested that H2A.Z is associated with the transcriptionally active genes. However, the mechanism of histone variant exchange and the effect in nucleosome is not clearly understood. We measured the stability of major H2A or histone variant H2A.Z containing nucleosome using Fluorescence resonance energy transfer (FRET). We found that variant H2A.Z containing nucleosomes are more stabile than canonical H2A nucleosomes. Another observation was that the nucleosome assembly protein 1 (NAP-1) from yeast facilitates the exchange of H2A-H2B or histone variant H2A.Z-H2B dimers into assembled nucleosomes. We also showed that transient removal of H2A-H2B dimers facilitates nucleosome sliding along the DNA to a thermodynamically favorable position. Histone exchange as well as nucleosome sliding is independent of ATP and rely on the presence of the C-terminal acidic domain of yeast NAP-1. Our results suggest a novel role for NAP-1 in mediating chromatin fluidity by incorporating histone variants and assisting nucleosome sliding. In the X-ray crystallography study, we found that the NAP-1 forms a homodimer with α-helix dimerization motif and concave β-sheet. In the NAP-1 structure, loop domains wrapping around adjacent α-helix stabilize the dimer structure. This helix loop - helix loop (HL-HL) dimer conformation may provide the strong stability of dimer structure. The conservation of concave β-sheet domain between yNAP-1 and other chaperones suggests that the histone chaperons share the similar structural motif, four-antiparalle strand motif. X-ray crystallography study of nucleosome assembly protein provides other insights into structure and function relationships.
Keywords: molecular biology; biophysics; biochemistry